Preparation and characterization of hydrophobic composite material from residues generated by incineration of modified textile waste - Jianzun Lu; Jiajun Chen; Sabrina Yanan Jiang; Chiu-Hong Lee; Yu Li; Huada Daniel Ruan (Next Materials)
This study introduces a novel approach to textile waste recycling, which involves modification of textile waste with a polyvinyl alcohol (PVA) oxidizing agent before incineration. The primary research question addressed is whether this modification can enhance the stability and hydrophobicity of textile waste residues, thereby transforming them into a potentially valuable product. The methodology employed involves a comprehensive microstructural analysis using XRD, FTIR, SEM-EDS, BET surface area, and particle size analyzers. Moreover, water contact angle measurement was conducted to assess the hydrophobicity of the residues. The key findings of this study indicate that the residues from modified textile waste demonstrated much higher stability and hydrophobicity by the formation of homogeneous amorphous carbon resulted in aggregation, which exhibited a dense structure and superior water resistance compared to the residues from nonmodified textile waste. The formation of aggregate and the higher water contact angles for both modified natural (134°) and synthetic (117°) textile waste residues than for nonmodified ones (62° and 113°) indicate that the modification process has enhanced the hydrophobicity of textile waste residues. The potential value of this study lies in its contribution to sustainable waste management and creation of valuable products from solid waste.